Relationships between maternal behavior, maternal attachment, acculturation, locus of control and social anxiety among iranian primary school children in Kuala Lumpur, Malaysia - Hashempour, Sara (2016)
In recent decades, social anxiety among children has become considerably more common phenomenon in behavioural science research. Numerous studies have investigated the underlying factors of social anxiety among children. Nonetheless, very few researches have focused on this problem among immigrants’ children. This study examined the effect of maternal behaviours (support, behavioural control, and psychological control) and maternal attachments on child social anxiety among Iranian primary school children living in Kuala Lumpur Malaysia. The study also examined the mediating role of locus of control in the relationships between maternal behaviours and maternal attachment with social anxiety. As this study is among Iranian children who came temporarily to foreign country, acculturation of these children in new country as well as background information such as age, gender, number of sibling and length of stay in Malaysia have been considered. This study is a quantitative study on 227 female and male primary school children aged between 9 and 12 years old selected through systematic random sampling technique. Data was collected using self-administered questionnaire such as Child Report of Parenting Behavior Inventory (CRPBI-30), by Schludermann and Schludermann (1988), Parent and Peer Attachment-Revised IPPA-R (Gullone & Robinson, 2005), Children's Nowicki-Strickland Internal-External Locus of Control Scale, by Nowicki & Strickland (1973), the Social Anxiety Scale for Children - Revised (SASC-R) (La Greca & Stone, 1993) and Iranian (Persian) Self Identity Scale by Khanideh (2007). All the instruments used in this study were highly reliable. Descriptive statistics, independent sample t–test, and regression analysis were conducted; while the mediating effect was estimated using Barron and Kenny (1986) approach. The result of independent sample t–test showed that female respondents demonstrated higher social anxiety than male. The result of multiple linear regression analysis showed that almost all variables in regression model, except maternal support were significant predictor of social anxiety. The result also showed that, locus of control partially mediated the relationships between maternal behavioural control, maternal psychological control and maternal attachment with social anxiety. However, the relationship between maternal support and social anxiety was not mediated by locus of control. In conclusion, the findings of the present study revealed the importance of mothers in enhancing locus of control and preventing social anxiety of primary school children in Malaysia. The nature of relationships between independent variables and social anxiety implied that social anxiety is prevalent among children abroad. Reasonable control and secure attachment may have a significant effect on child’s locus of control and reducing their social anxiety. The finding of this study can help mothers to monitor their own behaviors while living abroad in order to enhance the quality of their children’s life. Also, the present results have significant recommendation for future research and practice. However, this study is limited to primary school children in Malaysia, aged between 9 and 12 years old. Thus, the researcher recommends further study in other region and difference age group to enhance the generalizability.